Operating Performance of Public Banks in Taiwan after Privatization - Liu, Z-John (Information Management and Business Review, 2013)
The study selected nine state-owned banks in Taiwan that went on privatization in 1998 and foreign banks with similar assets scales and more branches in Taiwan as sample. Data Envelopment Analysis (DEA) is applied to explore the variation condition of efficient values for the periods between 1995 and 2007, prior and after each state-owned bank became privatized. To avoid data bias, the years affected by financial storm (from 2008 to 2010) were eliminated. Empirical results of the study are: The number of branches and assets return ratio are positively correlated to overall technical efficient value; savings and government holding ratio are negatively correlated to overall technical efficient value, showing that government releasing stock holdings through privatization can actually improve bank operating efficiency. The result of MannWhitney non-parametric examinations show that: Before the state-owned banks in Taiwan privatized, their average operating efficiency is significantly lower than that of foreign owned banks. After privatization, there is no significant difference in operating efficiency between state-owned and foreign-owned banks, revealing that privatization has effect of enhancing operating efficiency in public banks.